2021
DOI: 10.14744/tjtes.2021.90453
|View full text |Cite
|
Sign up to set email alerts
|

A 10-Year Retrospective Analysis of Intimate Partner Violence Patients in the Emergency Department

Abstract: BACKGROUND: Intimate partner violence (IPV) is an important human rights problem faced by one in three women worldwide. The aim of this study is to evaluate the demographic, trauma, and radiological characteristics of patients admitted to a tertiary emergency department due to IPV. METHODS: Sociodemographic characteristics (age, gender, education level, and marital status), trauma characteristics (severity, type, and location), radiological imaging findings (radiography, computed tomography, and magnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…Four studies focused on the general patterns of orthopaedic injury seen in survivors of IPV and characterized location of injury by upper or lower extremity. Our data support historical trends that upper extremity fractures are the second most common fracture in IPV victims 6,7,11,12 . Around one-third of the IPV cohort studied by Jospeh et al identified extremity fractures as a presenting injury.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…Four studies focused on the general patterns of orthopaedic injury seen in survivors of IPV and characterized location of injury by upper or lower extremity. Our data support historical trends that upper extremity fractures are the second most common fracture in IPV victims 6,7,11,12 . Around one-third of the IPV cohort studied by Jospeh et al identified extremity fractures as a presenting injury.…”
Section: Resultssupporting
confidence: 88%
“…Thomas et al supported this, finding 5 of 6 (83%) subacute or chronic fractures were in the hand 16 . Kavak et al reported 5.7% of patients with IPV history had chronic healing fractures characteristic of IPV 7 . The most common chronic fracture or evidence of a previous fracture was seen in the phalanges, followed by the radius and ulna.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations